Douglas John Hall : Collected Readings - Hall, Douglas John, 1928- (Book collections on Project MUSE., 2014)
Hall's work takes the measure of Christian belief and doctrine explicitly in light of North American cultural and historical experience. Hall's theological insights challenge churches to embrace change and develop genuine community, uncompromised theology, and honest engagement with the larger culture. To a failed culture and a struggling church Hall shows the radical implications of a theology of the cross for the shape and practice of church, preaching, ministry, ethics, and eschatology.